Bolivar and the writers - Maria Baralt, Rafael; Muñoz Vicuña, Elìas (Revista Universidad de Guayaquil, 1983)
The best writers in Latin America have written about Bolivar. We publish pages of Rafael Maria Baralt, Venezuelan, 1810-1860; Juan Montalvo, Ecuadorian 1832-1889, and José Martí, Cuban, 1853-1895.